SUSTAINABLE CONSUMPTION IN CONSUMER BEHAVIOUR OF YOUNG POLISH SINGLES - Zalega, Tomasz (Acta Scientiarum Polonorum. Oeconomia, 2020)
This article is a research exercise and refers to the consequences of singlehood in the context of environmental consumer behaviour. It essentially seeks to provide some insight into sustainable consumption in consumer behaviour of young singles in Poland, based on the results of the author’s own research. Following that research, the focus was on verifying whether young people living alone correctly understand sustainable consumption and to what extent they therefore implement its assumptions in their consumer behaviour. In addition, the relationship between lifestyle and environmental consumer behaviour of young singles was analysed, as was their knowledge of eco-labels placed on products. The basis for conclusions is provided by the research material collected in the survey conducted in a sample of 826 young singles.